A Comparison of Academic Outcomes and Students’ Satisfaction in Offline, Online, and Blended Teaching Models - Maemunah Sa'diyah; Ira Patriani; Anita Lontaan; Afdaleni Afdaleni; Made Suandika (AL-ISHLAH: Jurnal Pendidikan, 2023)
Blended learning is an alternative solution that the government had come up with to make up for the flaws of online learning, which was put into place during COVID-19 when the offline way of teaching was completely switched. In practice, though, the online method had some problems, so the government came up with a plan to use the mixed learning method. Then, this study was done to see how offline, online, and blended learning models affected learning results and how happy students were with them. The qualitative method was used to do this study. The information used in this study came from 28 students at X University who filled out surveys and were also interviewed. Overall, the results of this study showed that the face-to-face learning approach was the most effective way to learn. This is because students can understand the lessons better and feel more satisfied with this way of learning. Other learning models, on the other hand, have more distractions, making it harder for students to understand the lesson and making them feel like it's hard to follow the teaching process, making students less happy in the end.